Requirement elicitation: identifying the communication challenges between developer and customer - Che Pa, Noraini; Mohd Zin, Abdullah (The Society of Digital Information and Wireless Communications, 2011)
Eliciting requirements for a system is an important activity in requirement engineering. This process occur at the early stages in system development which involves communication between customers and developers. Researchers have identified that poor communication is one of the most common problem in identifying and defining customer’s requirements. This problem will contribute to bad result e.g. poor system, failure of the system and budget overruns. The communication is challenging and difficult as this process also includes cognitive aspect, personalities, techniques and tools. A study was carried out to explore the communication challenges that are faced by developers and customers during software requirement elicitation in Malaysia. The results of this study had shown that there are some important communication challenges during software requirements elicitation process in Malaysia. In addition, most of the practitioners were pursuing the practices that have been traditionally used by the organizations. Consequently, the results of this study have given us a good incentive to expand our research in the area of software requirements elicitation.